Essays on socioemotional skills and learning - OLIVEIRA, Felipe Resende (2018)
This thesis is composed by two articles in Applied Microeconomics - Economics of Education.The first chapter seeks to measure the effect of bullying in math scores of students in the 6th grade of public school in the city of Recife, Pernambuco, Brazil with the use of data from a survey by Joaquim Nabuco Foundation in 2013. The methodology applied is Propensity Score Matching (PSM) in order to compare students who reported having suffered bullying with a control group, consisting of students who did not suffer bullying. Specifically, I aim to understand the role of social emotional skills and their potential influence on bullying. The results suggest that bullying has a negative impact on performance in mathematics and that social emotional skills can help students deal with bullying. Several econometric techniques were used to circumvent endogeneity problems. To identify personality traits, we use a factor model that also serves to correct for prediction error bias. The sensitivity analysis indicated potential problems of omitted variables. The results indicate that anti-bullying programs should take into account social emotional skills.In the second chapter, I discuss that there are scarce but relevant researches stating the importance of educating socioemotional competencies to the youth as it impacts individual’s success in life, and what is even more scarce is the analysis of the results and impact of programs that work towards that educational goal, either implemented though public policies and Government funded projects. This chapter seeks to evaluate the impact of the Academia Educar Project in 2016, focusing on its’ development of socioemotional skills on students using the methods of Propensity Score Matching and Differences in Differences. Positive and significant effects were found on Sociability (12% of initial value), Assertiveness (16% of initial value) and Political Participation (double the initial percentage of treaties interested in participating in the country's policy). The results for Locus Control and Imaginative variables were significant and in the direction expected only in part of the specifications; for Volatility, the results do not suggest impact. Several robustness analyzes were performed to validate the results found.